2020
DOI: 10.1002/acm2.12871
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural networks for automatic segmentation of thoracic organs‐at‐risk in radiation oncology – use of non‐domain transfer learning

Abstract: Purpose: Segmentation of organs-at-risk (OARs) is an essential component of the radiation oncology workflow. Commonly segmented thoracic OARs include the heart, esophagus, spinal cord, and lungs. This study evaluated a convolutional neural network (CNN) for automatic segmentation of these OARs. Methods: The dataset was created retrospectively from consecutive radiotherapy plans containing all five OARs of interest, including 22,411 CT slices from 168 patients. Patients were divided into training, validation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In this study, the performance of AccuContour TM -based and denoising-based auto-segmentation was below a satisfactory level for the esophagus. Previous studies have reported that the DSCs of deep-learning-based auto-segmentation do not exceed 0.8 for the esophagus [ 40 , 46 , 47 , 48 , 49 ]. Due to the absence of a consistent intensity contrast between the esophagus and neighboring tissues in non-contrast CT images, the boundaries between the esophagus and surrounding soft tissues are not well-defined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the performance of AccuContour TM -based and denoising-based auto-segmentation was below a satisfactory level for the esophagus. Previous studies have reported that the DSCs of deep-learning-based auto-segmentation do not exceed 0.8 for the esophagus [ 40 , 46 , 47 , 48 , 49 ]. Due to the absence of a consistent intensity contrast between the esophagus and neighboring tissues in non-contrast CT images, the boundaries between the esophagus and surrounding soft tissues are not well-defined.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some researchers proposed to integrate the knowledge about how features should behave in generating prediction as attribution priors into DL training (33). Finally, noting that some knowledge learned from relative domains is also informative for the target tasks, transfer learning is an effective approach to leverage such knowledge in DL training (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent approaches for CT lung segmentation show a clear predominance of learning algorithms capable of directly learning the distribution of the data used for training. Methodologies inspired on U-net [ 154 ] cover the majority of deep learning-based attempts [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 ]. To increase the complexity of the feature extraction task, the encoder module could reuse transferred weights from pre-trained networks, as in the works by Vu et al [ 163 ] and Jalali et al [ 166 ], where the VGG-16 and ResNet-34 models were adopted to work as encoder blocks, respectively.…”
Section: Computer-aided Decision Systemsmentioning
confidence: 99%
“…Methodologies inspired on U-net [ 154 ] cover the majority of deep learning-based attempts [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 ]. To increase the complexity of the feature extraction task, the encoder module could reuse transferred weights from pre-trained networks, as in the works by Vu et al [ 163 ] and Jalali et al [ 166 ], where the VGG-16 and ResNet-34 models were adopted to work as encoder blocks, respectively. More investigations on improvements in typical convolutional blocks can also be found, integrating residual blocks [ 164 , 167 ], inception modules with dense connections [ 162 ], and squeeze-and-excitation blocks to target specific thoracic organs at risk [ 165 ].…”
Section: Computer-aided Decision Systemsmentioning
confidence: 99%